‘Florida-07’, a Medium Maturity, Large Seeded, High Oleic Peanut Variety with Resistance to Tomato Spotted Wilt - Barry L. Tillman; Daniel W. Gorbet (EDIS)
SS-AGR-313, a 3-page fact sheet by B.L. Tillman and D.W. Gorbet, describes this variety of peanut released in 2006 because of its outstanding pod-yield potential, competitive grades, high oleic oil chemistry. Includes a table detailing the performance of runner market-type peanut varieties in Florida locations in the past four years. Published by the UF Department of Agronomy, November 2008. Reviewed May 2012.